MODERN TRENDS IN THE DEVELOPMENT OF UV-SOURCES OF GERMICIDAL RANGE - Бугаев Александр Степанович (Вестник московского государственного областного университета. Серия: Физика-математика, 2017)
In recent decades the field of application of UV light sources has been rapidly increasing. They can be used for many purposes in everyday life, medicine, industry, especially for disinfection of air, water, and surfaces. The most efficient for this purpose is the UV radiation within the so-called germicidal range. The mercury-vapor low and medium pressure lamps are most widely used. However, nowadays a tendency has been promoted to withdraw mercury appliances not only from household usage, but from industry. This leads to a necessity of the development of mercury-free UV light sources such as excimer lamps and UV light-emitting diodes (UV-LEDs). Recently a new kind of lamps, so called cathodoluminescent UV light sources (especially with field emission cathodes), has been developed.